Theatre of the oppressed: linking research, political commitment and pedagogical perspectives - Alessandro Tolomelli (INTERthesis)
The intellectual path of Augusto Boal was parallel to his life course. “A path making by walking”, we can say using Machado’s words. This article wants to be an example of how important is the connection between personal experience and research process in the field of education, as it was for me before as educator as well as education sciences researcher, later. Education, politics, social research are fields very related to each other. In my personal experience, working as educator I discovered the necessity of a pedagogical framework to sustain the practice; thinking as pedagogist I realized the important of the politic meanings of education; acting as Theatre of the Oppressed practitioner I understood the importance of keeping linked theory and praxis, personal and academic research. Summarily, in this paper I try to carry out some connecting points between pedagogy, politics and research using the method of the Theatre of the Oppressed as framework. The first part described the reasons of my interest on Pedagogy of the Oppressed (P. Freire) and then on Theatre of the Oppressed (A. Boal).  Later on, the focus is put on the meaning of the words ‘theatre’ and ‘oppression’ to explain the aims and the roots of the Theatre of the Oppressed. In the end of the paper, it is described the project “TOgether”, an European research-action path aimed to build up a curriculum for the Theatre of the Oppressed trainer as well as to experiment the aesthetics potential of the method.